Guardianship and Property Management in Persons with Mental Illness: A Legal Overview: A Practical Perspective on Limited Guardianship under the Mental Healthcare Act 2017 and the Rights of Persons with Disabilities Act 2016 - Dr. Magesh Rajagopal (Tamil Psychiatry Journal, 2026)
Persons with mental illness often face significant challenges in society, particularly in areas such as access to treatment, protection of personal rights, and management of property and finances. Although the Mental Health Act of 1987 marked an important step in India, it had notable limitations, especially in safeguarding patient autonomy and human rights. This led to the enactment of the Mental Healthcare Act, 2017, which emphasizes patient rights and supported decision-making. In addition, Section 14 of the Rights of Persons with Disabilities Act, 2016 introduced the concept of “Limited Guardianship,” promoting a collaborative approach where decisions are made jointly with the affected individual, respecting their capacity. This article provides an overview of different forms of guardianship, including Nominated Representative, Limited Guardianship, and Plenary Guardianship. It particularly focuses on practical challenges related to property management and financial decision-making for persons with mental illness. The paper also highlights gaps, ambiguities, and areas requiring policy and legal refinement in the current framework.